Eggshell as an additive in concrete mix - Hafifi Hafiz, Hassan (2014)
An investigation on the performance of eggshell in concrete has been tested and carried out. Four proportions of concrete specimens were used in this research which is 0%, 5%, 10%, and 15%. In this concrete the material was used are Portland cement, chicken eggshell, coarse aggregate, fine aggregate, and optimum of water. The maximum size of the coarse aggregate is 20 mm and sizes of eggshell are between 2 mm - 5 mm. The test that has been conducted is slump test, compressive strength test, flexural test and water penetration test. From the investigation, eggshell concrete in compressive strength has achieved the objectives of this project where the value of 28 days compressive strength more than control. In this research also shows the measurement of slump test in medium workability which is suitable and affordable for concrete grade 20. Besides that, concrete with 5% eggshell additive achieve the highest compressive strength which is 28 N/mm2. The eggshell concrete also improves in flexural strength which is the highest strength is 7.93 N/mm2 and water penetration test produce a best of performance with lower depth at 14 mm only. The optimum eggshells concrete are suitable in typical reinforced concrete application in building which intended working life is at least 50 years.